Usability Analysis of Educational Assistance Information Systems Using the Heuristic Evaluation and End User Computing Satisfaction (EUCS) Methods. - Angel Novita Sinurat; Anggyi Trisnawan Putra (Journal of Advances in Information Systems and Technology, 2024)
User interface and user satisfaction are crucial components of a system that can significantly impact its usability. SIBADIK, as a web-based application used by many students as a scholarship platform, should have a high level of usability. However, there has been no specific research analyzing the usability of the SIBADIK website. Usability analysis is necessary to determine whether the website is acceptable to users or if there are issues that need to be addressed. The method used is heuristic evaluation combined with End-User Computing Satisfaction (EUCS) to measure user satisfaction levels before and after improvements. The sample was obtained using purposive sampling technique with Slovin formula at 10% margin of error, resulting in 95 samples. The research findings indicate that the SIBADIK website received a user satisfaction score of 2.92 (in the "fairly satisfied" category). The heuristic evaluation by three evaluators revealed a severity point of 3.0195 (rounded to 3), indicating a major usability problem that requires improvements. Twelve issues were identified on the SIBADIK website: 2 issues with Match Between System and Real World, 1 issue with User Control and Freedom, 2 issues with Consistency and Standards, 1 issue with Error Prevention, 2 issues with Recognition Rather Than Recall, 2 issues with Flexibility and Efficiency of Use, and 2 issues with Aesthetic and Minimalist Design. These identified problems serve as recommendations for improving the SIBADIK user interface.